Expect Success, Get Success: How Self-fulfilling Prophecy Can Impact New Product DevelopmentLeaders who help their product development teams build and sustain confidence can create expectations of success that translate into improved success of new products. Issue 4 (16th May 2021) - Watson, Amy; Obal,, Michael; Kannan, Rangapriya (Priya)
Abstract: Overview: In new product development (NPD), practitioners and researchers have explored a variety of organizational factors, such as market orientation and firm innovativeness, that drive product success. They have not explored the role of expected outcomes on NPD. Using a social psychology perspective—a hitherto missing perspective in the NPD literature—we describe how expected outcomes can drive new product success. Specifically, we highlight how self-fulfilling prophecies are likely to impact the performance of new products favorably. Surprisingly, our results indicate that expected outcomes mediate the relationship between predicted product success and actual success, leading to improved new product performance. Introducing a social psychological perspective can impact how innovative firms accomplish new product success.